Exercise Training in Patients with Stable Chronic Heart Failure - Butterfield, J.; Faddy, S.; Davidson, Patricia; Ridge, B. (Lippincott Williams & Wilkins, 2008)
Recent Evidence has suggested that patients with stable chronic heart failure (CHF) may respond favourably to a progressive exercise program. The use of noninvasive hemodynamic monitoring and B-type natriuretic peptide (BNP) measurement in these patients is not well reported. This study investigated the utility of noninvasive hemodynamic monitoring and point-of-care BNP in a cardiac rehabilitation outpatient setting. Both BNP and noninvasive hemodynamic monitoring can be utilized in the cardiac rehabilitation outpatient setting and seem to mirror the favourable response to exercise of other functional tests.